The Problematic of Low Class Students' Low Interest in Reading - Fahira Sinaga; Nabila Ananda (Berpusi Publishing, 2024)
This research aims to describe a literature review regarding the problem of low interest in reading among lower grade students . This research is a literature review. Data collection techniques were taken from various published articles and journals, both accredited and non-accredited. From the articles and journals that became references, there were 10 articles and journals that matched the title of the research. digital literacy needs to be considered in increasing interest read elementary school students. In the second journal, based on results study is known that in an effort to increase elementary school students' interest in reading, students should be given support so that the interest in reading emerges from themselves and introduced to reading materials so that students get used to reading, therefore the reading habits of students when they are in elementary school will foster a stronger interest in reading. high until the students grow up The articles used as reference material were published in 2014-2023. the Problem of Low Interest in Reading in Lower Class Students. Published articles and journals, both accredited and non-accredited, from the articles and journals that are references, there are 10 articles and journals that match the title of the research.Based on results study is known that low interest read because many factors and problems that occur with students class low.